BUDIDAYA JAMUR PERUSAK KAYU I. PENGARUH PENAMBAHAN DEDAK TERHADAP PRODUKSI JAMUR TIRAM - Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Oyster mushroom (Pleurotus ostreatus) was cultivated on sawdust of four wood species, i.e. teak (Tectona grandis L.f.), rubber (Hevea brasiliensis .Muell. Arg.), kemang (Mangifera caesia Jack) and meranti merah (Shorea johorensis Foxw.) mixed with rice bran containing 5 %, 10 %, 15 %, 20 %, 25 % by weight and distilled water, The substrate was cooled after autoclave sterilization before being inoculated with pure culture of oyster mushroom. The mature mushrooms were harvested daily after the growth of fruiting body.Relative high yield was obtained from rubber (146.92 g) and kemang (122.77 g), the lower yield was obtained from teak (73.84 g) and the lowest from meranti merah (58.82 g) per 500 g media. .Rice bran supplement seems to improve mushroom yield. The lowest yield i.e; obtained from sawdust substrate mixed with 5 % rice bran (65.78 g). Rice bran supplementation of 10 - 25 % gave non significant different yield (80.30 - 88.86 g) per 500 g media.The average Biological Efficiency (BE) of entire treatments were obtained from rubber 64.27 % (45.24 - 79.84 %) and kemang 61.66 % (56.84 - 74.25 %). The lower BE was obtained from teak 29.53 % (25.86 - 33.92 %) and meranti merah 24.70 % (0 - 40.22 %).